Designing and Manufacturing of Vegetable Slicing Machine - Msuya, Juma N. (Tanzania Journal of Engineering and Technology, 2025)
Agro-processing industry is faced with a challenge of slicing of vegetables for immediate consumption. This stems from the fact that the traditional slicing methods use bare hands, and knives. This method is faced with shortcomings of inefficiency, poor hygiene, and significant dangers to injury. If vegetables are not sliced, their drying takes longer, may possibly be spoiled, and cannot be stored for future uses. Therefore, this paper strives to design a vegetable slicing machine to increase the efficiency of the drying process as a post-processing step. The study employed a Pugh’s design model to design the machine and manufacture it. First, the necessary information for the design was collected. Thereafter, the machine was designed according to specifications – 0.5 hp, 1400 rpm motor; with a capacity of slicing of 30 kg/h, at an efficiency of 86%. The prototype was tested using carrots. The whole testing was conducted with no injury, and ease to the users. It is advised to automate the vegetable feeding process and reduce the size for future improvements of the vegetable slicing machine.